-5-9b=-6b

Simple and best practice solution for -5-9b=-6b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5-9b=-6b equation:


Simplifying
-5 + -9b = -6b

Solving
-5 + -9b = -6b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '6b' to each side of the equation.
-5 + -9b + 6b = -6b + 6b

Combine like terms: -9b + 6b = -3b
-5 + -3b = -6b + 6b

Combine like terms: -6b + 6b = 0
-5 + -3b = 0

Add '5' to each side of the equation.
-5 + 5 + -3b = 0 + 5

Combine like terms: -5 + 5 = 0
0 + -3b = 0 + 5
-3b = 0 + 5

Combine like terms: 0 + 5 = 5
-3b = 5

Divide each side by '-3'.
b = -1.666666667

Simplifying
b = -1.666666667

See similar equations:

| 3m+7n=6p | | 19=r-(-9) | | 2.6-0.2b=4.1-0.5b | | p-1/4=3/8+0.5p | | (2b+1)(2b-1)= | | 2x+5+-3x+1=2x+5 | | 42x-1=5x+2 | | 1+cosx=0 | | p-1/4=3/8+1/2 | | Y=6x-4x^2 | | 46+g*9/09876=678,467+345 | | 8y+24=6y+36 | | 3x-8=3+6 | | 15-9=12x-7x-3x | | 3x=6.4 | | 2160000=300*s | | x(x-5)=5(x-5) | | 8x+3=11x | | 2160=300*s | | 7(x-4)-(4x+5)=4(x-5)-9 | | 15+3x=8x+4 | | x^5-3x^4+3x^3-x^2=0 | | 7-4(x-1)=x+1 | | x+3(0)=9 | | 3(-3)-5x=11 | | 0.50x+0.05(10-x)=0.10(-67) | | z-15=y | | 0.08x-0.05(100-x)=0.20 | | -6r=12 | | 4x+2y=80 | | (-1)+3y=9 | | 64-6x=12x+20 |

Equations solver categories